A Y-chromosomal study of mansi population from konda River Basin in Ural. Issue 1 (December 2019) - Pamjav, H; Dudás, E; Krizsán, K; Galambos, A
Abstract: Based on genetic studies published, the Hungarian Y-chromosomal gene pool significantly differs from other Uralic-speaking populations. Hungarian males possess a high frequency of haplogroup R1a-Z280 and a low frequency of haplogroup N-Tat, which is uncommon among other Uralic-speaking populations. Previously we published the Northern and Southern Mansi Y-chromosomal data and now further studied to search the links between the linguistically related Hungarian populations. Samples were collected from 36 Southern Mansi males from Konda river basin in the Ural region. We analysed male-specific markers including Y-STRs and Y- SNPs, which would reflect past and recent paternal genetic history. In the case of the Southern Mansi males, the most frequent haplogroups were N1b-P43 (33%), N1c-L1034 (28%) and R1a-Z280 (19%). For phylogenetic studies, networks were constructed for the most frequent haplogroups in the Konda Mansi together with Khanty and Hungarian speaking populations. The Konda Mansi population shared common haplotypes within haplogroups R1a-Z280 or N-M46 with Hungarian speakers, which may suggest that the Hungarians were in contact with the Mansi people during their migration to the Carpathian Basin.